2023
DOI: 10.1111/1471-0307.12939
|View full text |Cite
|
Sign up to set email alerts
|

Butter fortified with spray‐dried encapsulated Ferulago angulata extract nanoemulsion and postbiotic metabolite of Lactiplantibacillus plantarum subsp. plantarum improves its physicochemical, microbiological and sensory properties

Abstract: Butter is a valuable dairy product, and its sensory attributes can be changed due to oxidative rancidity and microbial contamination. This study investigated the effect of Ferulago angulata extract nanoemulsion (FAEN) on butter properties alone or in combination with postbiotic metabolites produced by Lactiplantibacillus plantarum subsp. plantarum (PMLP) into the butter in the free form or spray-dried encapsulated. The combination of the encapsulated form of FAEN and PMLP in butter indicated that it is capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The common pH of the human colon varies between 6.0 and 8.0 [77], and in the negative control (IC), no significant differences (p > 0.05) were observed after 48 h. On the other hand, FOS presented a high decrease from 7.15 to 3.64, and in the straw extract, pH decreased from 7.24 to 6.72 (Figure 3). The pH decrease, although slight, may create a favorable environment for the reproduction of some beneficial bacteria while inhibiting harmful microorganisms.…”
Section: Impact Of Postbiotics On Gut Microbiota Modulationmentioning
confidence: 94%
“…The common pH of the human colon varies between 6.0 and 8.0 [77], and in the negative control (IC), no significant differences (p > 0.05) were observed after 48 h. On the other hand, FOS presented a high decrease from 7.15 to 3.64, and in the straw extract, pH decreased from 7.24 to 6.72 (Figure 3). The pH decrease, although slight, may create a favorable environment for the reproduction of some beneficial bacteria while inhibiting harmful microorganisms.…”
Section: Impact Of Postbiotics On Gut Microbiota Modulationmentioning
confidence: 94%
“…These treatments had a significant effect on the sensory properties and increased the shelf life of High-moisture mozzarella cheese up to eight days during 16 days of storage at 7°C. Anvar et al (2023a) developed a functional butter with Ferulago angulata extract nanoemulsion (FAEN) alone or in combination with postbiotic metabolites produced by Lactiplantibacillus plantarum subsp. plantarum (PMLP) in the free form or spray-dried encapsulated (en-FAEN and en-PMLP).…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…They found that under heating conditions of 40°C, 50°C and 60°C, astaxanthin-fortified flaxseed oil showed the lowest lipid oxidation rate compared with the control group as the heating time increased. Many studies have also demonstrated the positive effects of other types of antioxidants on the oxidative stability of butter and sour cream (Ahmadi et al 2017;Alipour et al 2023;Anvar et al 2023).…”
Section: Introductionmentioning
confidence: 99%